Aortic Arch Hypoplasia in Infants: Algorithm of Diagnosis and Treatment - I. Truba; I. Dzyurii; L. Prokopovych; V. Lazoryshynets (Ukrainian Journal of Cardiovascular Surgery, 2020)
Background. Aortic arch hypoplasia is a congenital anomaly of the development of the aortic arch characterized by hemodynamically significant narrowing of one or more segments of the aortic arch. Despite the great interest in the problem of aortic arch hypoplasia, there are many contradictions in terms of terminology and classification. It is quite difficult to draw a clear line between normal physiology and pathology to determine in which cases there is a true hypoplasia, so, from a practical standpoint, the fundamental issue is the selection of criteria with reference to which we can talk about clinically and prognostically significant aortic arch hypoplasia. Important and yet controversial are the issues of multi-stage treatment of aortic arch hypoplasia and concomitant congenital heart diseases (CHD), and, in case of the isolated variant of hypoplasia, the choice of surgical approach.The aim of the study was to discuss different strategies and surgical approaches for patients with aortic arch hypoplasia, with an emphasis on surgical solutions and based on many years of experience, to develop an algorithm for diagnostic and surgical treatment of the aortic arch hypoplasia in infants.Conclusions. Aortic arch hypoplasia in infants remains a complicated issue in pediatric cardiac surgery. The variety of anatomical forms of isolated aortic arch hypoplasia and common overlap with other CHD raises many questions for the cardiac surgeon. Decisions concerning diagnosis and choice of further treatment tactics made in the neonatal period will affect not only the immediate but also the long-term outcome in the future. The algorithm of diagnostic and patient management with aortic arch hypoplasia allows to make the right timely decision which will affect the outcome of surgical treatment of this complex pathology.